O ensino de História e as novas tecnologias: questões de métodos e o ensino-aprendizagem de História em protagonismo discente - SILVA JÚNIOR, João Batista da (Universidade Federal do Pará, 2023)
This master's thesis analyzes the possibility of using of using educational applications as a didactic resource in a high school classroom. The general aim was to identify and critically analyze the contents, methodologies and the effectiveness of applications that explore computer networks, providing contents from the discipline History, identifying the extent to which these contents and methodologies propose an innovative proposal in the construction of historical knowledge. For the effectiveness of the proposal, analyzes were made regarding the role of historical narratives in the teaching of history and the training of history teachers in educational technologies. We also observed, through the students' narratives, the extent to which this extra classroom knowledge that emerges outside the classroom space is or is not part of the historical consciousness of these students. We discussed how these didactic resources can be propositional in the formation of a didactic of history through interviews, narrative construction and participant observation. As a result, we presented an educational product built by the students of the Escola Estadual de Ensino Fundamental e Médio do Outeiro, a 3rd year high school class, a virtual application with content produced by these students about their locality, which has the potential to become an interesting didactic tool for the production and dissemination of historical knowledge.